Use of pulsed electric field permeabilization to extract astaxanthin from the Nordic microalga Haematococcus pluvialis. (October 2019) - Martínez, Juan Manuel; Gojkovic, Zivan; Ferro, Lorenza; Maza, Marcos; Álvarez, Ignacio; Raso, Javier; Funk, Christiane
Highlights: Permeabilization efficiency of H. pluvialis cells depended on growth conditions. Pulsed electric field followed by incubation efficiently extracts astaxanthin. PEF triggers an intracellular enzymatic process facilitating the extraction. Abstract: The Nordic microalgal strain Haematococcus pluvialis was exposed to various stress conditions to induce astaxanthin accumulation. Highest carotenoid content (19.1 mg·g −1 dw ) was achieved in nitrogen-free culture medium at a high light intensity. The efficiency of Pulsed Electric Field (PEF) pre-treatment of stressed fresh biomass of H. pluvialis followed by incubation in the growth medium was compared to classical disruption methods (bead-beating, freezing-thawing, thermal treatment or ultrasound) for the subsequent extraction of astaxanthin in ethanol. N-starved cells treated with PEF followed by aqueous incubation for 6 h resulted in extraction of 96% (18.3 mgcar ·gdw −1 ) of the total carotenoid content compared to 80% (15.3 mgcar ·gdw −1 ) using other physical methods. The proportion of free forms of astaxanthin was higher in PEF-treated samples compared to mechanical disruption, suggesting PEF triggering an esterase activity. PEF pre-treatment of the cells followed by incubation in growth medium improved astaxanthin extraction in the eco-friendly solvent ethanol.